Microscopic Nuclear Reaction Models: Bridging Microscopic Theory and Nuclear Data. In Memory of Eric Bauge - Dupuis Marc (EPJ Web of Conferences)
A major goal in the field of nuclear reaction modeling has been to move from phenomenological models to predictive, microscopic theories—a central focus at CEA/DAM since the mid-1970s. A significant milestone in achieving this objective was reached in the early 1980s with the first applications of the JLM folding model by Lagrange et al., using HF and RPA ground and transition densities, and later deformed HFB densities. From the mid-1990s, E. Bauge advanced these efforts by encouraging and systematically applying them, playing a key role in advancing the field. These developments include detailed methods to describe direct reactions, such as elastic and inelastic scattering, and pre-equilibrium emission. This work has greatly improved our understanding of direct reactions in nuclear structure studies and laid the foundation for practical applications, benefiting users from astrophysical modelers to energy specialists. Building on the foundational work of researchers worldwide, and in particular the contributions of pioneers from CEA/DAM such as D. Gogny, M. Girod, Ch. Lagrange, and J.-P. Delaroche, Eric’s vision helped bring long-standing efforts to fruition. Today, his former students and collaborators continue these efforts, integrating results from various nuclear structure approaches into reaction studies, supported by the international partnerships he fostered. This has helped encourage similar advancements in other laboratories and supported a collaborative legacy that continues to drive the field forward.